Analisis Pengaruh Islamic Branding Terhadap Loyalitas Pelanggan di Ismart Retail Ponorogo - Fajar Surya Ari Anggara; Alamsyah, Nandy (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
Ismart Ponorogo is a retail store that is managed based on Islamic principles. Congregational ownership managed professionally and centrally to maintain competitiveness in terms of distribution networks, products, prices, and promotions. This research aims to test and explain the influence of Islamic brands on customer loyalty to Ismart Ponorogo. The research uses explanative research methods conducted through data collection in the field in a quantitative approach. The assumptions used in this study are variables that can be measured using respondents' responses to questionnaires, the consumer population of Ismart Ponorogo, and a sample of 67 respondents, data analysis using linear regression statistical methods, and hypothesis testing. Based on the results of the research shows that Brand Islami can increase customer loyalty to Ismart Ponorogo. This research has a novelty compared to previous research by testing Islamic brands to customer loyalty in retail stores managed based on sharia principles. Keywords: Islamic Brand, Customer Loyalty, Sharia Retail Shop